Sport Tourism: Impact of Ranto Canyon - Ali Priyono; Indra Prabowo; Indrayogi Indrayogi; Nugroho Susanto (Universitas Majalengka, 2024)
Researchers look at how tourism affects the economy, particularly in the sports sector, when there are tourist attractions nearby. Qualitative research methods with informants who have been determined using purposive sampling and random sampling methods. Collecting data with good observation through literacy, interviews, questionnaires, documentation and so on as supporting research data. The results of the study show that the development of sports tourism in Ranto Canyon uses the concept of sport tourism by utilizing natural resources which besides enjoying the beautiful green open nature can also do physical sports activities. Sports organized for visitors are rafting and body rafting which are facilitated by the involvement of the community as a guide and security team. The direct impact of sports tourism on the community's economy includes providing employment opportunities in the tourism sector and MSME business opportunities in selling their products to tourists, which indirectly increases tourism's contribution to local revenue and increases the income of small traders, opportunities for MSMEs to introduce the product